Parental haplotype-specific single-cell transcriptomics reveal incomplete epigenetic reprogramming in human female germ cells - Ábel Vértesy (Nature Portfolio, 2018)
In mammalian female germ cells, parent-specific epigenetic marks are erased and the X chromosome reactivated before entry into meiosis. Here, by combining parental haplotype reconstruction with single-cell transcriptomics of human female embryonic germ cells, the authors demonstrate that epigenetic reprogramming occurs in a heterogeneous fashion and during a broad time window up to week 14.